Student’s Perception on the Impact of Digital Literacy on Reading Comprehension - Amaliah, Ismi; Usman, Sriati; Lebagi, Desrin; Maf’ulah, Maf’ulah (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to explore students’ perceptions of the impact of digital literacy on reading comprehension among English Education students at Tadulako University. A descriptive, qualitative approach was employed, involving the distribution of questionnaires to students in the 2023 cohort and in-depth interviews with selected participants. The findings reveal that students generally perceive digital literacy as having a positive influence on their reading comprehension. Digital tools such as online dictionaries, translation applications, and diverse online reading materials help students understand texts more easily and increase their motivation to read. However, challenges such as internet connectivity issues, distractions, eye strain, and difficulties in evaluating reliable sources were also reported. Overall, digital literacy is viewed as a supporting factor that enhances reading comprehension when accompanied by critical thinking skills and proper guidance. The study highlights the importance of integrating digital literacy instruction into reading courses to optimize students’ comprehension in digital learning environments.